2020
DOI: 10.1074/jbc.ra119.011650
|View full text |Cite
|
Sign up to set email alerts
|

Intramitochondrial proteostasis is directly coupled to α-synuclein and amyloid β1-42 pathologies

Abstract: Mitochondrial dysfunction has long been implicated in the neurodegenerative disorder Parkinson’s disease (PD); however, it is unclear how mitochondrial impairment and α-synuclein pathology are coupled. Using specific mitochondrial inhibitors, EM analysis, and biochemical assays, we report here that intramitochondrial protein homeostasis plays a major role in α-synuclein aggregation. We found that interference with intramitochondrial proteases, such as HtrA2 and Lon protease, and mitochondrial protein import si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 92 publications
1
21
0
Order By: Relevance
“…Approaches to improve the cellular environment, as can be achieved by hypoxic conditioning, are expected to represent a superior approach to target mitochondrial dysfunction in neurodegeneration [ 174 ] as compared to targeting specific downstream consequences of mitochondrial damage, in approaches targeting, for example, ROS or ATP levels in HD [ 215 , 216 ]. Hypoxic conditioning by itself is limited in many regards; age [ 217 ] and disease may blunt adaptive physiological and molecular adaptations and the selection of the hypoxic dose is a balancing act due to the danger inherent to severe hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches to improve the cellular environment, as can be achieved by hypoxic conditioning, are expected to represent a superior approach to target mitochondrial dysfunction in neurodegeneration [ 174 ] as compared to targeting specific downstream consequences of mitochondrial damage, in approaches targeting, for example, ROS or ATP levels in HD [ 215 , 216 ]. Hypoxic conditioning by itself is limited in many regards; age [ 217 ] and disease may blunt adaptive physiological and molecular adaptations and the selection of the hypoxic dose is a balancing act due to the danger inherent to severe hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning approaches can be applied to strengthen mitochondrial functions, increase the endogenous oxidative stress defense and reduce neuroinflammation [ 173 ], processes that are all central in HD pathogenesis (see below). Such strategies are able to improve brain tissue resilience and thus brain cell health, which has been suggested to be an important feature of future neurodegeneration treatment strategies with greater translational potential than previous strategies developed in pre-clinical models [ 174 ]. Furthermore, the relatively early average onset as compared to sporadic neurodegenerative diseases render HD an attractive target for conditioning approaches, particularly if conditioning is confirmed to be less efficient in older persons, as discussed in Section 3 .…”
Section: Conditioning Benefits On Mitochondrial Dysfunctions Oxidmentioning
confidence: 99%
“…In addition, identified mutations in the HTRA2 gene cause hereditary tremors in humans which can progress into Parkinson’s disease [ 168 , 169 , 170 ]. Furthermore, HtrA2 has been found to co-localize with α-synuclein within Lewy bodies, and it could be shown that HtrA2 can reduce the propensity of α-synuclein seeding while also aiding the removal of already aggregated α-synuclein [ 45 , 171 , 172 ]. In addition, the proteolytic activity of HtrA2 is affected by PINK1, another protein whose dysfunction is linked to Parkinson’s disease.…”
Section: α-Synuclein Processing By Mitochondrial Proteins: a Facilmentioning
confidence: 99%
“…Another evolutionally conserved mitochondrial protease is the hexameric Lon protease, which plays an important role in clearing oxidatively damaged proteins in mitochondria and which has been found in high concentrations in the substantia nigra of patients with Parkinson’s disease. It has also demonstrated an ability to reduce the aggregation propensity of α-synuclein [ 45 ]. Specifically, inhibiting Lon protease with small molecule inhibitors led to an attenuation of α-synuclein aggregation in a cell culture model [ 45 , 176 ].…”
Section: α-Synuclein Processing By Mitochondrial Proteins: a Facilmentioning
confidence: 99%
See 1 more Smart Citation